2009
DOI: 10.1093/hmg/ddp057
|View full text |Cite
|
Sign up to set email alerts
|

Notch signaling contributes to the pathogenesis of human osteosarcomas

Abstract: Notch signaling plays an important role in developmental processes and adult tissue homeostasis. Altered Notch signaling has been associated with various diseases including cancer. While the importance of altered Notch signaling in cancers of hematopoietic and epithelial origins has been established, its role in tumors of mesenchymal origin is less clear. Here, we report that human osteosarcoma cell lines and primary human osteosarcoma tumor samples show significant up-regulation of Notch, its target genes and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
138
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(148 citation statements)
references
References 24 publications
9
138
1
Order By: Relevance
“…Studies thus far on the Notch pathway in osteosarcoma are rather limited. (31,32) Metastases A defining feature of osteosarcoma is the high rate of metastasis that results from the primary bone tumor disseminating to distant secondary sites by a hematogenous route. Despite the use of multimodality and multiagent systemic cancer therapy before and after management of the primary tumor, the vast majority of deaths seen in osteosarcoma patients occur as a result of metastases.…”
Section: Etiology Of Osteosarcomamentioning
confidence: 99%
“…Studies thus far on the Notch pathway in osteosarcoma are rather limited. (31,32) Metastases A defining feature of osteosarcoma is the high rate of metastasis that results from the primary bone tumor disseminating to distant secondary sites by a hematogenous route. Despite the use of multimodality and multiagent systemic cancer therapy before and after management of the primary tumor, the vast majority of deaths seen in osteosarcoma patients occur as a result of metastases.…”
Section: Etiology Of Osteosarcomamentioning
confidence: 99%
“…(38) However, several reports have shown that osteoblast cells expressed Notch1, and BMP-2 did not have an appreciable effect on Notch1 expression. (39)(40)(41) Moreover, osteoblast differentiation can occur despite Notch1 expression. For this reason, it was expected that Notch1 signaling could be modulated during osteoblast differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…Some recent studies have demonstrated the transcriptional activation of MMP9 and uPA by Notch1 in human prostate cancer 19 and the participation of Notch1 signaling in pancreatic cancer 20 and osteosarcoma. 21 In breast cancer, the suppression of E-cadherin expression occurs through the Jagged1-Notch1-Slug EMT pathway. 22 In human HCC, EMT and tumor metastasis are not well defined, although Twist, a down-stream transcription factor of the EMT pathways, has been found to be positively correlated with metastasis and down-regulation of E-cadherin.…”
mentioning
confidence: 99%